Measuring design innovation for project-based design assessment: considerations of robustness and efficiency (2017)
Instructional approaches that support the acquisition of innovation design process skills for engineering and other design students are critical to developing design competencies. Resources that enable efficient and valid evaluation of design outcomes are needed; however current evaluation methods do not apply well to the heterogeneous projects found in authentic project-based design classes such as capstone design. We develop a robust and efficient measure of design outcome innovation and validate our measure with a large and diverse set of design outcomes from a project based design class. The measure is based on expert judgments of designconcepts’ value and functionality derived from a set of importance-weighted design requirements. In the context of an engineering design class, the innovation score was a statistically significant predictor of success in terms of implementation status by the client. Thus, the measure’s validity was supported by its ability to predict design concepts’ implementation by clients in the context of a product realization class. New design outcome assessment measures in the context of authentic project-based design environments, such as the one developed in the present study, should interface with process-based metrics to create higher-quality input into the overall assessment of design team performance.